Tabiat Maling Kepot: Kereta Bayi Anti Maling dengan Kendali Posisi Tangan - Agastia, Naufal; Aji, Pramuditya Purba; Wantoro, Enrico Maulana; Anggraheni, Herlambang Dianisa; Fitryan, Novia Aulia Nor (JTET (Jurnal Teknik Elektro Terapan), 2017)
In this era, thereâs so much automatic system used to help human. An example is take care of baby. Taking care baby isnât easy, Especially when bring baby to go to somewhere outside, we will need a device namely baby stroller. But in fact, baby stroller weâve meet still used humanâs power and less of protection. TABIAT MALING KEPOT is a baby stroller anti thief that move used motor DC and controlled wirelessly using bluetooth based on hand position through a modul thereâs accelerometer. This modul used in wrist. Baby stroller will go forward, backward, turn left or right based on hand tilt detected by accelerometer. Equipped with a seat belt that can locked by motor servo. With power supply Lipo 12 V 2200mAH, this device can work until an hour. TABIAT MALING KEPOT can bring max load 15 Kg with average speed 0.5 m/s till 1 m/s.Â  On baby stroller there are also Ultrasonic and Proximity sensor used to detect obstacle in front of baby stroller. So when there are obstacle in front of baby stroller, the baby stroller will stop automatic.Key Words : Accelerometer,Â  Motor DC, Motor Servo, Proximity, Ultrasonic, WirelessÂ